psychological connotations in the form of pessimism in the Abbased poetry (Journal of Hama University, 2024)
This research is based on the study of psychological connotations in the form of pessimism, pessimism is one of the most prominent and rooted phenomena in the human soul, which was and still yearns to see the unseen, and to predict the consequences of things before doing it, it is necessary to define the most prominent search terms, and the highlight On the most prominent psychological indications manifested in the image of pessimism, which emerged through many techniques followed by some Abbasid poets, including: (words in the image of pessimism, pessimism from people, psychological connotations in the image of astronomy and nature), which reflected the emotional state they wanted to convey to the recipient and influence him from through it.